Informed consent, and an ethico-legal framework for paediatric observational research and biobanking: the experience of an Italian birth cohort study. - Toccaceli, Virgilia; Serino, Laura; Stazi, Maria Antonietta (Cell Tissue Bank, 2014)
Birth cohort studies are important tools for life-course epidemiology, given the spectrum of the environmental, behavioural, and genetic factors that should be considered when making judgements on human health. Biobanks are valuable components of studies designed to investigate the genetic variability of diseases and improve phenotypic characterisation. In studies involving vulnerable populations and biobanks, it is essential to provide ethical reasoning and analyse the legal requirements. We describe the processes and the tools used in the iterative design of an appropriate informed consent model and the ethico-legal framework of the Piccolipiù study. The Piccolipiù study is a prospective population-based study funded by the Italian Ministry of Health that intends to enrol 3,000 newborns and their mothers in five Italian cities, and to store biological samples for future use. To realise these objectives, we performed a thorough evaluation of the literature, of national and international guidelines, and of the impact of the Italian legal requirements for research biobanking. Discussions among stakeholders facilitated the design of the informed consent and the ethico-legal framework. Several topics are addressed, including the suitability of a broad informed consent for paediatric biobanks, infant vulnerability, access to and sharing of data, and the disclosure of individual's genetic results. Discussion of the ethical and legal procedures adopted in epidemiological biobanking might be a fruitful ground for comparison both at the national level, where standardization and homogeneity are lacking, and at the international level, where different regulatory issues are often in the background and might hamper research biobanks networking.
Keywords: Cohort Studies; Confidentiality; Databases, Genetic; Genetic Privacy; Genetic Research; Genotype; Humans; Infant, Newborn; Information Dissemination; Informed Consent; Internationality; Italy; Parents; Phenotype